Redesigning corporate identity for Batu Laut homestay / Liyana Gapar - Gapar, Liyana (Faculty of Art and Design, 2013)
This chapter gives the explanation about early process of this academic writing. This whole process consist of finding the solution for branding Batu Laut Homestay, to know the impact level of new direction and also to promote Batu Laut Homestay as one of the suitable places for vacation attractions in Malaysia. Other than that, researcher will do the literature review for the past studies and journals that contains four stages, which are background research and literature reviews, Objectives and research methodology, Analysis and findings and Conclusion and Recommendation.Each and every stage has its own purpose and contents.For the first stage, background research and literature reviews focuses on the level impact of new direction in corporate identity to promote Batu Laut Homestay as one of the vacation places in Malaysia, where theoretical study is conducted through literature, references and reviews on written materials such as journals, previous research reports, books, newspapers or via the internet to have a better understanding of research topic. References also involve acts, plans and any secondary data that is related to the study. Early reviews are also conducted in this stage to identify problems. Any information obtained will be used as a reference to provide a form of observation. After that, in second stage, Objectives and Research Methodology Researcher will state the research objective and approach towards the solution for branding Batu Laut Homestay. Besides that, researcher will include the research methodology to find the problems.